The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/ahe.12154
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Morphometric Variations in the Arterial System of the Domestic Cat

Abstract: We document the anatomical architecture and frequency of occurrence of variations in the branching pattern of the brachiocephalic artery and the origin of the internal iliac arteries in the domestic cat, a widely used model organism in both anatomical training and research. Based on the study of 56 preserved specimens, we observed three distinct arrangements in the branching pattern of the brachiocephalic artery. The most common pattern (52% of the examined specimens) was that in which the brachiocephalic arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…The available literature provides only one publication on the detailed morphology of the brachiocephalic trunk in a domestic cat (11). The conducted study showed the presence of three types of branches of the said vessel.…”
Section: Resultsmentioning
confidence: 96%
“…The available literature provides only one publication on the detailed morphology of the brachiocephalic trunk in a domestic cat (11). The conducted study showed the presence of three types of branches of the said vessel.…”
Section: Resultsmentioning
confidence: 96%
“…It has been reported in the mustelids L. longicaudis (Barbosa et al., 2021), Lontra canadiensis (Baitchman & Kollias, 2000), Lutra lutra (Jang et al., 2023) and Mustela putorius furo (Quesenberry & Carpenter, 2012); the procyonids Procyon cancrivorus (Pereira et al., 2016; Santos et al., 2004), Procyon lotor (Davis, 1964), Nasua nasua (Biihrer et al., 2015), Nasua sp. (Davis, 1964) and Potos flavus (Davis, 1964); the ailurid Ailurus fulgens (Davis, 1964); the ursids Ailuropoda melanoleuca, Helarctos malayanus , Ursus americanus , and Ursus arctos gyas (Davis, 1964); the canids Canis lupus familiaris (Davis, 1964; Hermanson et al., 2020), Canis latrans, Lycaon pictus (Davis, 1964), Vulpes vulpes (Davis, 1964; Karakurum & Özgel, 2013) and Cerdocyon thous (Engel et al., 2013; Lima et al., 2016), and the felids Felis catus (Gonzalez et al., 2015; More et al., 2016) and Leopardus pardalis (Martins et al., 2010). Among these species, the anomalous origin of the right subclavian artery has been reported in C. lupus familiaris in very low prevalence, such as 1.1% (3/275) (Vitums, 1962), 0.8% (7/802) (Sebastian‐Marcos et al., 2019) and 1.6% (3/192) (Schorn et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Aortic arch (AA) branching patterns represent diverse variations among mammalian species, including carnivores [ 1 2 3 ], rodents [ 4 5 ], primates [ 6 ], pigs [ 7 ], horses [ 8 ], and ruminants [ 9 10 11 ]. Each species has distinctive features [ 12 ].…”
Section: Introductionmentioning
confidence: 99%